Creating Social Change in and Through Intercollegiate Sport - E. Nicole Melton (Journal of Intercollegiate Sport, 2015)
The purpose of this paper is to introduce the work included in the special issue: Creating Social Change in and Through Intercollegiate Sport. In doing so, the author develops a multilevel conceptual model, demonstrating how the research included in the special issue addresses the antecedents and outcomes of social change initiatives in intercollegiate sport at the macro (i.e., institutionalized practices, cultural norms), meso (i.e., support of others, compelling narratives, collaborations) and microlevel (i.e., perspective-altering experiences, attitudes toward role of sport) of analysis. In addition, the author suggests ways to overcome barriers and increase the success of future social change initiatives. Based on this collection of scholarship, the author encourages researchers and practitioners to consider the multilevel factors that influence social change and the subsequent outcomes of such actions.